2013
DOI: 10.1097/ico.0b013e3182542613
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Inhibitors for Treatment of Corneal Neovascularization

Abstract: Our results suggest that both topical and subconjunctival bevacizumab achieve significant reduction in the area of corneal NV. This meta-analysis provides an evidential basis for the new therapeutic concept of treating corneal NV with antiangiogenic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 60 publications
1
41
0
1
Order By: Relevance
“…[17][18][19][20] It is hypothesized to enable a more persistent and longer lasting VEGF blockade, and a number of studies have shown that intravitreal aflibercept is more effective than the conventional anti-VEGF agents. [17][18][19][20] If intravitreal aflibercept could penetrate the retinal surface and the entire retinal thickness to induce regression of corneal NV, [16][17][18][19] topical aflibercept administration would probably permeate and penetrate the ocular surface to induce regression of corneal NV and modulate the neovascular process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19][20] It is hypothesized to enable a more persistent and longer lasting VEGF blockade, and a number of studies have shown that intravitreal aflibercept is more effective than the conventional anti-VEGF agents. [17][18][19][20] If intravitreal aflibercept could penetrate the retinal surface and the entire retinal thickness to induce regression of corneal NV, [16][17][18][19] topical aflibercept administration would probably permeate and penetrate the ocular surface to induce regression of corneal NV and modulate the neovascular process.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,15,16 As VEGF plays a crucial role in the creation of corneal NV, its treatment with anti-VEGF antibodies seems to be the right method, and it has been proven in numerous studies using subconjunctival and topical anti-VEGF, such as bevacizumab and ranibizumab. 11,[18][19][20] A novel anti-VEGF, named aflibercept, has gained popularity since its approval from the Food and Drug Administration in 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF-A blockade has recently been validated as an effective strategy for the inhibition of new blood vessel growth in cancer and ocular pathologies. Anti-VEGF therapy was indicated to be effective in the inhibition of corneal NV [4,5,6,7,8]. However, several studies have also shown that anti-VEGF therapy may not be effective in the treatment of established unwanted blood vessels, suggesting that these vessels may become less dependent on VEGF-A for survival.…”
Section: Introductionmentioning
confidence: 99%
“…7 Several clinical investigations have shown the efficacy of ranibizumab in the treatment of corneal neovascularization. [8][9][10] Aflibercept is a newly developed anti-VEGF agent that combines a truncated form of fms-like tyrosine kinase (Flt), kinase insert domaincontaining receptor (KDR), and the Fc portion of human immunoglobulin G. 11 Studies have reported potent antiangiogenic effects of aflibercept after topical or subconjunctival administration. [12][13][14] The objective of this study was to compare the effects of 3 anti-VEGF agents (bevacizumab, ranibizumab, and aflibercept) on corneal epithelial cell viability and wound healing using human corneal epithelial cells (HCECs).…”
Section: Introductionmentioning
confidence: 99%